2006
DOI: 10.1364/oe.14.005558
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating sub-nm closed loop MEMS flattening

Abstract: Ground based high-contrast imaging (e.g. extrasolar giant planet detection) has demanding wavefront control requirements two orders of magnitude more precise than standard adaptive optics systems. We demonstrate that these requirements can be achieved with a 1024-Micro-Electrical-Mechanical-Systems (MEMS) deformable mirror having an actuator spacing of 340 microm and a stroke of approximately 1 microm, over an active aperture 27 actuators across. We have flattened the mirror to a residual wavefront error of 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…Extensive work has been done by our colleagues in detailing the challenges of the working with our MEMS device 23 and in fundamental system limitations when using the PSDI as a direct-phase sensor to flatten the MEMS. 20 Readers seeking detailed discussions on matters such as the voltage calibration of the MEMS or the various ways in which an actuator misbehaves should consult those papers. We will focus here on the WFS leg and FTR.…”
Section: Performance Results With Reference Slopesmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive work has been done by our colleagues in detailing the challenges of the working with our MEMS device 23 and in fundamental system limitations when using the PSDI as a direct-phase sensor to flatten the MEMS. 20 Readers seeking detailed discussions on matters such as the voltage calibration of the MEMS or the various ways in which an actuator misbehaves should consult those papers. We will focus here on the WFS leg and FTR.…”
Section: Performance Results With Reference Slopesmentioning
confidence: 99%
“…The PSDI does not see zero phase; is sees a residual error e psdi of typically 0.6 nm RMS in band. 20 The MEMS is held with this shape and the WFS takes a slope measurement. In practice, our reference slopes still have some level of error on them, due to transients such as WFS noise and air currents on the bench.…”
mentioning
confidence: 99%
“…These mirrors were tested at BMC and also extensively at the LAO. [5][6][7][8][9][10] The final, winning design was based on the actuator used in the BMC 140 MEMS. This actuator has a total stroke of more than 4 microns (for the center of a 3 × 3 actuator patch) along with excellent surface quality of less than 5 nm RMS surface print-through and actuator scalloping.…”
Section: Development Of Mems Dmmentioning
confidence: 99%
“…For example, see section 3.2 of Evans et al 8 During our most recent development, we have worked with both 1K and 4K DMs that have several types of abnormal actuators.…”
Section: Abnormal Actuatorsmentioning
confidence: 99%
“…Evans et al have shown that the MEMS can be controlled in closed-loop to sub-nm accuracy with direct phase measurements. 6 This can also be done 7 with a spatially filtered Shack-Hartmann wavefront sensor and the Fourier reconstructor. Morzinski et al have shown that MEMS actuator position is highly repeatable and temporally stable.…”
mentioning
confidence: 99%